Investigating Student Empowerment and Social Involvement: The Case of a Moroccan University - El Guermat, Abdel Moula (Journal for Teaching and Education for Scholars, 2026)
The voices of students in Moroccan universities are often being underrepresented,  that they often feel left out of decision-making processes related to their learning environment. This study attempts to highlight this problem by examining the relationship between student empowerment and social involvement among MA students at Mohammed I University in Oujda. To achieve this aim, the study adopts an exploratory sequential mixed-methods design, grounded in well-established frameworks such as Zimmerman’s Psychological Empowerment Theory; this latter is of utmost importance in understanding how an individual establishes a sense of empowerment within his environment, as well as that of Astin’s student involvement theory. The objective is to investigate students’ institutional voices and see how far they feel able to take part in university life and decision-making. Essentially, the study seeks to uncover critical factors that influence student agency and participation, with real-world implications for promoting more student-centered and inclusive learning environments. The findings are expected to support ongoing reforms in Moroccan universities that prioritize active learning and democratic student engagement.